Assessing the benefits of storage applied to energy communities - Ahmed, Sanjana (2019)
Community energy systems are an emerging concept which aims to re-organize the local energy system through efficient integration of Distributed Energy Resources (DERs) and engagement of local communities. A better understanding of the possible benefits of deployed DERs such as community energy storage systems is therefore required, along with an active energy management system within the control framework of community smart-grids, in order to integrate and optimize the operation of flexible resources within the energy communities. An efficient model of a community energy management system is proposed in this thesis for communities equipped with grid-connected PV and Battery Energy Storage System (BESS). An algorithm is developed which controls the power flow between the electricity end-users, the communal BESS and the power grid, based on historical and instantaneous PV generation and load consumption data attained from three real communities in the UK. Increased accessibility to smart-meters and market availability of Time-of-Use electricity tariff schemes, which amplifies off-peak/peak cost difference, are exploited to achieve energy cost minimization for energy end-users in the communities through energy-shifting and increment of PV self-consumption. The methods of choosing a battery size which balances the trade-off between increasing battery capacity and reducing system cost is demonstrated and their impact on the annual household electricity cost is assessed. Similarly the effects on energy loss and cost saving by choosing converter ratings which are lower than the maximum power of the system is demonstrated and using a method of power-bins, the rating is determined for each community. Assessment has been done on communities in the UK to develop an algorithm for a Community Power Flow Battery Management System (CPF BMS), and to better understand the benefits that battery energy storage, in particular centrally controlled systems, can bring to an energy community. The operation of loads clustered as a community as opposed to individual users has been assessed and the results show that community operation achieves higher energy cost savings. It also allowed for larger optimum battery and converter sizes, which in turn allows higher self-consumption of local PV generation, better energy-shifting from off-peak hours to high-tariff band periods through battery storage, and finally lower energy bills. This project contributes to the increasing number of technologies and business models focusing on the decarbonisation of the energy sector through cost reduction incentives to the electricity end-users, and empowering the community to have a greater control of their energy usage and resources.